Influence of different post estropausal models on dental socket repair, bone metabolism, and antioxidant capacity of C57Bl/6 J mice - Bacelar, Ana Carolina Zucon [UNESP]; Momesso, Nataira Regina [UNESP]; Biguetti, Claudia Cristina; Simionato, Gustavo Baroni [UNESP]; de Freitas, Rayara Nogueira [UNESP]; de Aguiar Silveira Meira, Juliana [UNESP]; Ortiz, Rafael Carneiro; Ervolino, Edilson [UNESP]; Chaves Neto, Antonio Hernandes [UNESP]; Matsumoto, Mariza Akemi [UNESP] (Springer Nature, 2025)
The objective was to analyze and compare the influence of different post estropausal models on dental socket repair, bone metabolism and antioxidant capacity of mice. 46 C57BL/6 J mice were divided in the following groups: NC (negative control)—no treatment, OVX-SHAM—sham ovariectomy, OVX—ovariectomy, VCD—medicated with 160 mg/kg/day of 4-vinylcyclohexene diepoxide via IP, and aged—post-estropausal. After persistent diestrus, they underwent extraction of the upper right incisor, euthanized after 7 and 21 days for microCT, histopathology, birefringence, immunohistochemistry, and biochemical analysis of bone and antioxidants markers. Sockets repaired after 21 days, showing distinct histological aspects. At day 7, NC and OVX-SHAM exhibited remodeling trabeculae, while OVX and Aged showed irregular trabeculae and poor cellularization at day 21. VCD showed discrete bone formation at day 7, undergoing remodeling at day 21. Moderate RANKL and OPG immunostaining was observed, mainly in leukocytes. VCD showed reduced BV/TV in at day 7 in comparison with all groups, except with OVX. Total TRAP and ALP and antioxidant capacity were significantly increased in Aged at 21 days compared to the others. No differences were detected considering calcium, phosphate and TBARs. The different estropause models did not impede dental socket repair but interfered in the quality of the formed bone, as well as in plasma levels of bone remodeling markers and antioxidant capacity. These particularities should be considered when selecting a post estropausal experimental model for the investigation of bone healing events.